The Shell Bitumen Handbook (Telford, 2003)
The Shell Bitumen Handbook has been regarded for many years as the authoritative source of information on bitumens used in road pavements. This new edition seeks to enhance that reputation. For over a hundred years Shell has been in the forefront of bitumen technology and continues to lead in research and development. The Shell Bitumen Handbook reflects this leading role. The handbook begins with basics. The manufacture, storage and handling of bitumen are explained, and followed by a comprehensive section on specifications and quality. Bitumen emulsions are dealth with in a special chapter. The mechanical testing and physical properties of bitumen, its structure and rheology, properties such as durability and adhesion, and the influence of these properties on performance in practice are all set out in individual chapters. A further chapter is devoted to the practice of enhancing the performance of bitumens by the addition of modifiers. Six chapters present aspects of asphalts. These chapters detail types of mixtures, their manufacture and testing, mechanical properties, transport, laying and compaction and mixture design. The analytical design of flexible pavements - a field in which Shell is particularly prominent - forms a chapter by itself, as does the technology of surface dressing. A miscellany of useful facts and figures rounds off the book. Since the last edition, there have been significant strides in a number of key areas of asphalt technology. These include the development of new mixtures, an improved understanding of the mechanisms by which pavements fail and the availability of high-performance bitumens. The Handbook has been fully revised to reflect these advances, as well as updating the standard procedures and methods which are necessary nowadays for those involved in using asphalts in an environment of ever-more demanding specifications. Compiled by the Shell Bitumen European Technical Team the Shell Bitumen Handbook is intended to be of faily use to civil engineers in pavement construction and maintenance, and also to students and researchers.